Metamorphic readings transformation, language, and gender in the interpretation of Ovid's Metamorphoses - Sharrock, Alison 1963-; Möller, Daniel 1974-; Malm, Mats 1964- (Oxford University Press, 2020)
Ovid's remarkable and endlessly fascinating 'Metamorphoses' is one of the best-known and most popular works of classical literature, exerting a pervasive influence on later European literature and culture. A vast repository of mythic material as well as a sophisticated manipulation of story-telling, the poem can be appreciated on many different levels and by audiences of very different backgrounds and educational experiences. As the poem's focus on transformation and transgression connects in many ways with contemporary culture and society, modern research perspectives have developed correspondingly. 'Metamorphic Readings' presents the state of the art in research on this canonical Roman epic. Written in an accessible style, the essays included represent a variety of approaches, exploring the effects of transformation and the transgression of borders
Includes bibliographical references and index
Keywords: Ovid / 43 B.C.-17 A.D. or 18 A.D. / Metamorphoses; Ovid / 43 B.C.-17 A.D. or 18 A.D. / Appreciation; Ovidius Naso, Publius -- v43-17 -- Metamorphoses; Sprache; Transformation; Geschlechterforschung; Konferenzschrift -- 2016 -- Stockholm